Revisiting the casing layer: Casing materials and management in agaricus mushroom cultivation - Dias, Eustáquio Souza; Zied, Diego Cunha [UNESP]; Pardo-Gimenez, Arturo (FapUNIFESP (SciELO), 2021)
The cultivation of button mushroom has reached a high technological level in developed countries and is associated with high productivity indices. This technological level involves not only compost production and crop management but also the casing layer. Peat has been established as one of the most appropriate casing materials for the cultivation of button mushroom due to its excellent properties. However, good-quality peat is not available in all countries, and peat is not renewable, which reinforces the need for alternative materials. Therefore, studies on the casing layer should include its response to the induction of fruiting since this stage is where the main changes that lead to the formation of primordia occur. This review addresses the different aspects of fruiting induction of Agaricus mushrooms and the influence of the characteristics of the casing layer on mushroom production.
Revisitando a camada de cobertura: Materiais e manejo da camada de cobertura no cultivo dos cogumelos agaricus
Keywords: Button mushroom; Fruiting induction; Peat; Royal sun mushroom